HOTS in teacher classroom interaction: A case study - Yuyun Yulia; Fenita Rizki Budiharti (Universitas Islam Sultan Agung, 2019)
As Goronga (2013) notes that classroom interaction encourages students to actively participate in teaching learning process. Teacher question plays an important role to trigger students' critical thinking or Higher Order Thinking Skills (HOTS). This paper highlights questions revealed in teaching learning process that triggering students' critical thinking. Class observation and interview is conducted and then analyzed based on Bloom’s taxonomy. Data eventually show that remembering is mostly uttered to stimulate the students to state what they know about the topic and recall particular information. This means teachers find difficulties to practice questions with HOTS aspects. Teachers need to have more practice on how to encourage students to have critical thinking as one of skills in this disruptive era.